NCERT Solutions for Class 12 Maths Exercise 7.8 hapter 7 Integrals – FREE PDF Download
NCERT Solutions for integrals Class 12 exercises 7.8 are accessible in PDF format which is available at CoolGyan’s online learning portal. The solutions to this particular exercise from chapter 7 Integrals have been prepared by our experts who have years of experience in this field. Students can find, well-explained solutions to maths problems at CoolGyan’s online learning portal. All the solutions are provided in a way that will help you in understanding the concept effectively. You can download them in PDF format for free.
NCERT Solutions for Class 12 Maths Chapter 7 Integrals (Ex 7.8) Exercise 7.8
Evaluate the following definite integrals as limit of sums:
1.
Ans. We know that
∫abf(x)dx=limh→0[f(a)+f(a+h)+f(a+2h)+...+f(a+(n−1)h)]∫abf(x)dx=limh→0[f(a)+f(a+h)+f(a+2h)+…+f(a+(n−1)h)]
where
Here, and
=
=
=
=
=
=
=
2.
Ans. We know that
∫abf(x)dx=limh→0h[f(a)+f(a+h)+f(a+2h)+...+f(a+(n−1)h)]∫abf(x)dx=limh→0h[f(a)+f(a+h)+f(a+2h)+…+f(a+(n−1)h)]
where
Here, and
=∫05(x+1)dx=limh→0h[1+(h+1)+(2h+1)+...+((n−1)h+1)]=∫05(x+1)dx=limh→0h[1+(h+1)+(2h+1)+…+((n−1)h+1)]
=limh→0h[n+h(1+2+3+...+(n−1))]=limh→0h[n+h(1+2+3+…+(n−1))]
=limh→0[nh+h2n(n−1)2]=limh→0[nh+h2n(n−1)2]
=limh→0[nh+nh(nh−h)2]=limh→0[nh+nh(nh−h)2]
=
=
= =
3.
Ans. We know that
∫abf(x)dx=limh→0h[f(a)+f(a+h)+f(a+2h)+...+f(a+(n−1)h)]∫abf(x)dx=limh→0h[f(a)+f(a+h)+f(a+2h)+…+f(a+(n−1)h)]
where
Here, and
=∫23x2dx=limh→0h[4+(4+4h+h2)+(4+8h+22h2)+...+(4+4(n−1)h+(n−1)2.h2)]=∫23x2dx=limh→0h[4+(4+4h+h2)+(4+8h+22h2)+…+(4+4(n−1)h+(n−1)2.h2)]
=limh→0h[(4+4+...n times)+4h(1+2+...+(n−1))+h2(12+22+....+(n−1)2)]=limh→0h[(4+4+…n times)+4h(1+2+…+(n−1))+h2(12+22+….+(n−1)2)]
=limh→0h[4n+4hn(n−1)2+h2n(n−1)(2n−1)6]=limh→0h[4n+4hn(n−1)2+h2n(n−1)(2n−1)6]
=limh→0[4nh+2nh(nh−h)+nh(nh−h)(2nh−h)6]=limh→0[4nh+2nh(nh−h)+nh(nh−h)(2nh−h)6]
=
=
= =
4.
Ans. We know that
∫abf(x)dx=limh→0h[f(a)+f(a+h)+f(a+2h)+...+f(a+(n−1)h)]∫abf(x)dx=limh→0h[f(a)+f(a+h)+f(a+2h)+…+f(a+(n−1)h)]
where
Here, and
=∫14(x2−x)dx=limh→0h[0+h+h2+2h+22h2+.....+(n−1)h+(n−1)2.h2)]=∫14(x2−x)dx=limh→0h[0+h+h2+2h+22h2+…..+(n−1)h+(n−1)2.h2)]
=limh→0h[h(1+2+3+..+(n−1))+h2(1++22+32.....+(n−1)2)]=limh→0h[h(1+2+3+..+(n−1))+h2(1++22+32…..+(n−1)2)]
=limh→0h[hn(n−1)2+h2n(n−1)(2n−1)6]=limh→0h[hn(n−1)2+h2n(n−1)(2n−1)6]
=limh→0[nh(nh−h)2+nh(nh−h)(2nh−h)6]=limh→0[nh(nh−h)2+nh(nh−h)(2nh−h)6]
=
=
= =
5.
Ans. We know that
∫abf(x)dx=limh→0h[f(a)+f(a+h)+f(a+2h)+...+f(a+(n−1)h)]∫abf(x)dx
=limh→0h[f(a)+f(a+h)+f(a+2h)+…+f(a+(n−1)h)]
where
Here, and
=∫−11exdx=limh→0h[e−1+e−1eh+e−1e2h+........+e−1e(n−1)h]
=∫−11exdx=limh→0h[e−1+e−1eh+e−1e2h+……..+e−1e(n−1)h]
[ The series within brackets is a G.P. and ]
So, We get
=limh→0 he−1[(eh)n−1]eh−1=limh→0 he−1[(eh)n−1]eh−1
=limh→0 he−1(enh−1)eh−1=limh→0 he−1(enh−1)eh−1
=limh→0 he−1(e2−1)eh−1=limh→0 he−1(e2−1)eh−1
=
=
=e−1e=e−1e
6.
Ans. We know that
∫abf(x)dx=limh→0h[f(a)+f(a+h)+f(a+2h)+...+f(a+(n−1)h)]∫abf(x)dx
=limh→0h[f(a)+f(a+h)+f(a+2h)+…+f(a+(n−1)h)]
where
Here, and
=∫04(x+e2x)dx=limh→0h[1+(h+e2h)+(2h+e4h)+........+((n−1)h+e2(n−1)h]=∫04(x+e2x)dx
=limh→0h[1+(h+e2h)+(2h+e4h)+……..+((n−1)h+e2(n−1)h]
=limh→0h[(h+2h+3h+......+(n−1)h)+(1+e2h+e4h+.....+e2(n−1)h]
=limh→0h[(h+2h+3h+……+(n−1)h)+(1+e2h+e4h+…..+e2(n−1)h]
=limh→0h[h(1+2+3+......+(n−1))+(1+e2h+e4h+.....+e2(n−1)h]
=limh→0h[h(1+2+3+……+(n−1))+(1+e2h+e4h+…..+e2(n−1)h]
[ The series within brackets is a G.P. and ]
=limh→0h[hn(n−1)2+1((e2h)n−1)e2h−1]=limh→0h[hn(n−1)2+1((e2h)n−1)e2h−1]
=limh→0[nh(nh−1)2+he2nh−1e2h−1]=limh→0[nh(nh−1)2+he2nh−1e2h−1]
=
=
=
=